Comparative transcriptome analysis reveals key candidate genes mediating ovarian development in Spodoptera frugiperda fed on two host plants - Zheng, Renwen; Yao, Ling; Peng, Jun; Chen, Zihan; Yang, Fan; Chen, Shuxian; Tang, Qingfeng (Frontiers in Physiology, 2022)
The fall armyworm (FAW), Spodoptera frugiperda, is a highly polyphagous lepidopteran pest, with its growth and adaptation affected by different host plants. However, little is known about the effects of host plants on ovarian development in this species. Thus, we evaluated the effects of feeding on corn (Zea mays L.) and goosegrass (Eleusine indica), on the ovarian development of S. frugiperda. Using various stages of S. frugiperda, we also evaluated the larval and pupal weights, number of eggs, and differentiation of ovarioles over time. Results showed that females fed on goosegrass had shorter ovarioles and laid less eggs than those fed on corn. Transcriptome analysis identified 3,213 genes involved in ovarian development in the fall armyworm. Of these, 881 genes were differentially expressed when fed on corn and goosegrass. The analysis also indicated that the hormone biosynthetic pathways may be involved in the reproductive system. In relation to the reproductive function, nine juvenile hormone (JH) biosynthetic genes, four 20-hydroxyecdysone (20E) biosynthetic genes, and four ovary-relevant functional genes were identified. The time course of the expression profiles of these hormone- and ovary development-related genes was measured by quantitative real-time PCR (qRT-PCR). In total, six of them showed a decreasing trend in the ovary of the FAW fed on goosegrass, while two genes showed an increasing trend. Our results showed that significant changes in the reproductive activity/ovary development in the FAW occurred in response to different diets. These results serve as bases for evaluating how optimal host plants and feeding preference affect ovarian development in the FAW.